Military Service and Lifetime Arrests: Examining the Effects of the Total Military Experience on Arrests in a Sample of Prison Inmates - Brooke, Erika J. (Criminal justice policy review, 2018)
Service in the military is an important event that may shape veterans’ life trajectories. Research has shown that military service is associated with increased risk of alcohol and substance abuse, mental illness, and antisocial behaviors, yet it remains unclear whether service places veterans at elevated risk of criminal justice involvement. In addition, most prior research treats military service as a dichotomous variable and does not consider the specific components of the military experience that might affect the impact that service has upon veterans. In the present study, a large sample of state prison inmates is utilized to test for the potential impact of military service, by itself, as well as age of entry, length of service, combat exposure, discharge type, and branch status on lifetime arrests. Results have implications for both military and criminal justice policies in ensuring that veterans have the assistance they need as they re-enter civilian life.